Organosolv lignin: A comprehensive review of pretreatment advancements and biorefinery integration - Melikoğlu, Mehmet (Elsevier, 2025)
This review synthesizes recent advancements in organosolv technology for the sustainable valorization of lignocellulosic biomass, focusing on optimizing the extraction process, comprehensively characterizing the resulting organosolv lignin (OSL), and exploring its multifaceted valorization. Significant progress in pretreatment encompasses novel solvent systems, reduced reaction severity, and a deeper understanding of delignification mechanisms, enabling efficient biomass fractionation into high-quality cellulose, hemicellulose, and OSL. Advanced characterization has elucidated intricate OSL structure-property relationships, which are crucial for tailoring its diverse applications. OSL is increasingly valorized into a wide array of high-value products, including bio-based chemicals (e.g., phenolic monomers), sustainable polymers, composites, and functional additives leveraging its antioxidant and antimicrobial properties. Future research directions emphasize process intensification, advanced predictive modeling, expanding high-value pathways, and holistic biorefinery integration. Ultimately, organosolv lignin is poised to become a cornerstone in fostering a circular, sustainable biobased economy by transforming agricultural and forestry residues into valuable resources.
Keywords: Organosolv Lignin; Lignocellulosic Biomass; Biorefinery